2022
DOI: 10.32322/jhsm.1052191
|View full text |Cite
|
Sign up to set email alerts
|

The factor analysis approach to mortality prediction in COVID-19 severe disease using laboratory values: a retrospective study

Abstract: Aim: Factor analysis is a statistical approach used mainly in social science scale development systems. The aim of this study was to evaluate the performance of factorial structures formed by laboratory values in predicting mortality in severe COVID-19 patients. Material and Method:The study included 281 patients diagnosed with ''severe coronavirus infection'' according to the WHO COVID-19 clinical management guideline who were treated in a 13-bed adult tertiary-level critical care unit of a tertiary level hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…CRP values above 130 mg/L were found to be associated with mortality. In our study, a statistically significant increase in CRP levels was found in the non-survivor group compared with the survivor group (p<0.001) (36)(37) In our study, a relationship between a decrease in albumin levels and mortality was shown. In addition, when clinically important variable logistic regression analysis was performed, it was observed that the albumin ratio was AUC 0.681 (95% CI: [0.621-0.742]; p<0.001), and albumin had high sensitivity in predicting mortality (84.5%).…”
Section: Discussionsupporting
confidence: 59%
“…CRP values above 130 mg/L were found to be associated with mortality. In our study, a statistically significant increase in CRP levels was found in the non-survivor group compared with the survivor group (p<0.001) (36)(37) In our study, a relationship between a decrease in albumin levels and mortality was shown. In addition, when clinically important variable logistic regression analysis was performed, it was observed that the albumin ratio was AUC 0.681 (95% CI: [0.621-0.742]; p<0.001), and albumin had high sensitivity in predicting mortality (84.5%).…”
Section: Discussionsupporting
confidence: 59%
“…B.1.1.7 variant has 17 mutations, including eight in the spike protein. Mutations affect the binding affinity to human angiotensin-converting enzyme 2 (ACE2) and entry into human cells which increase the infectivity (2)(3)(4) and changed the clinical presentation, morbidity and mortality of the disease (2,5,6). Due to the worse clinical presentation, we think that there may be differences in the radiological findings of the B.1.1.7 variant induced pneumonia compared to the Wuhan type.…”
Section: Introductionmentioning
confidence: 99%
“…The biochemical tests used routinely provide clinicians with important data about COVID-19. Many studies have been conducted to date on the effect of biochemical parameters on mortality in COVID-19 patients, and some risk factors have been found, such as comorbid diseases, D-dimer, and troponin (8)(9)(10)(11)(12). However, the number of publications evaluating the effect of arterial blood gases such as lactate, base excess, and bicarbonate on mortality is very few and the clinical consequences of these results during the first admission remain unclear.…”
Section: Introductionmentioning
confidence: 99%